Efektivitas Seminar Dan Praktik Dalam Meningkatkan Pemahaman Mahasiswa Tentang Sistem Pembiayaan Kesehatan - Aliyah Az Zahra Ibrahim; Rahmawati Rahmawati; Karmilasari Karmilasari (INDO PUBLISHING, 2026)
This study aims to analyze the effectiveness of seminar and practice activities in improving students' understanding of the health financing system. Method: The study used a quasi-experimental design with a one-group pretest-posttest design approach. The study sample was 17 students in the pre-test and 18 students in the post-test from the Health Administration Study Program, Sipatokkong Mambo University. The research instrument was a 15-question objective test. The intervention was carried out through a seminar with two presenters and a short practice. The normality test using Shapiro-Wilk showed that the pre-test data was normal (p = 0.170) but the post-test was not normal (p = 0.000). Data were analyzed using Independent Samples T-Test with SPSS. The Levene test results showed unequal variances (F = 9.534, p = 0.004). The t-test with equal variances not assumed produced t = -4.735, df = 21,054, p = 0.000 (p <0.05). The average pre-test score of 10.65 (SD=1.498) increased to 12.50 (SD=0.618) on the post-test, with a mean difference of 1.85 points. There was a significant difference in student understanding before and after participating in the health financing seminar and practice, indicating that the combined seminar and practice method effectively improved student understanding.